2012
DOI: 10.3844/ajbbsp.2012.157.163
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF <i>CATHA EDULIS</i> ON INSULIN, RESISTIN AND CORTISOL LEVELS IN TYPE-2 DIABETICS AND NON-DIABETICS

Abstract: In this study, the biochemical effects of Catha edulis leaves chewing (as psycho stimulant and aphrodisiac) on the serum concentration of resistin, insulin, cortisol, zinc, calcium, copper and blood glucose in both healthy individuals and type 2 diabetic patients were examined. 80 male subjects aged 35-55 years were recruited in this study, 40 of them were previously diagnosed as type 2 diabetics and the other 40 were healthy non-diabetics. The above two groups were subdivided into two subgroups (n = 20) in ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Additionally, cathinone reduces the activity of enzymes that metabolize free radicals, intensifying oxidative stress, which is a critical factor in the onset of diabetes and its complications. 38,39 In this study, people with a history of khat chewing were 2.32 times more likely to have DPN compared to non-chewers. This finding is comparable with a meta-analysis and cross-sectional studies done in Saudi Arabia and Yemen.…”
Section: Discussionmentioning
confidence: 64%
“…Additionally, cathinone reduces the activity of enzymes that metabolize free radicals, intensifying oxidative stress, which is a critical factor in the onset of diabetes and its complications. 38,39 In this study, people with a history of khat chewing were 2.32 times more likely to have DPN compared to non-chewers. This finding is comparable with a meta-analysis and cross-sectional studies done in Saudi Arabia and Yemen.…”
Section: Discussionmentioning
confidence: 64%
“…Reduced calcium concentration was reported in subjects with depression (41) and depression was more common subjects administered with khat (10 & 42). However, another study indicated that the serum calcium level was significantly increased among normal subjects and diabetic patients who chewed khat (43).…”
Section: Discussionmentioning
confidence: 99%